2019
DOI: 10.1002/ecy.2594
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment tolerance to increased temperature present across multiple kelp clades

Abstract: Kelp systems dominate nearshore marine environments in upwelling zones characterized by cold temperatures and high nutrients. Worldwide, kelp population persistence and recruitment success generally decreases with rising water temperatures coupled with low nutrients, making kelp populations vulnerable to impending warming of the oceans. This response to climate change at a global scale, however, may vary due to regional differences in temperature variability, acclimation, and differential responses of kelp spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…Reproduction potential and early life-history stages of many seaweeds are temperature-sensitive (Bartsch et al, 2013;Andrews et al, 2014), and increased temperatures can both suppress or enhance reproduction and recruitment success (de Bettignies et al, 2018;Muth et al, 2019). Following the 1982/83 El Niño, the turf-forming Pelvetia fastigiata and the canopy-forming fucoid Sargassum muticum showed increased recruitment success at La Jolla, California (Gunnill, 1985), which led to elevated abundances and likely shifted competitiveness News articles were only included if results were not yet published in peer-reviewed journals.…”
Section: Ecological Performancementioning
confidence: 99%
“…Reproduction potential and early life-history stages of many seaweeds are temperature-sensitive (Bartsch et al, 2013;Andrews et al, 2014), and increased temperatures can both suppress or enhance reproduction and recruitment success (de Bettignies et al, 2018;Muth et al, 2019). Following the 1982/83 El Niño, the turf-forming Pelvetia fastigiata and the canopy-forming fucoid Sargassum muticum showed increased recruitment success at La Jolla, California (Gunnill, 1985), which led to elevated abundances and likely shifted competitiveness News articles were only included if results were not yet published in peer-reviewed journals.…”
Section: Ecological Performancementioning
confidence: 99%
“…However, despite localized kelp declines, there is no unifying global pattern of kelp change, with some populations remaining unchanged and others expanding over the past half century 6 . Based on studies at early life-history stages, it is predicted that warm-adapted kelp populations existing at the equatorial range limits of species distributions may be the most resilient to climate change and most likely to persist into the future 7 . Longitudinal field observations at the range limits of kelp species are required to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The familiar sporophyte phase of Nereocystis is primarily an annual, with a holdfast that attaches to coarse substrates, a long stipe connected to a terminal buoyant bulb, and blades that proliferate on the water surface. The sporophyte has an obligatory alternate phase, a microscopic gametophyte, whose ecology is poorly understood and may be vulnerable to different environmental factors than the macroscopic sporophyte [12,35,36]. Limited research has shown that Nereocystis populations within Puget Sound are genetically distinct from populations on the exposed coast [37], and they host a distinct microbiome [38].…”
Section: Introductionmentioning
confidence: 99%
“…In field studies, concentrations of 10 µM were associated with thicker blade tissues and a lower rate of blade erosion in Macrocystis sporophytes[132]. Laboratory studies showed increased performance in microscopic stages of Nereocystis associated with DIN increases from 1 to 15 µM[36]. Nitrogen requirements may be greater during periods of rapid growth or elevated temperatures[133].…”
mentioning
confidence: 97%
See 1 more Smart Citation